CHIEF CARL BRASSHEAR’S STRUGGLE AGAINST RACISM IN MEN OF HONOR MOVIE - NURSANI, KHARISMA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Racism of colored people has become a peculiar issue recorded in thehistory of America. The practice of racism has made a great impact in every socialaspect between white American and the African-American citizen. At that time,colored people were oppressed by racial discrimination and injustice treatment.Some were struggling to get their rights, as it is portrayed in Men of Honor movie.It is a true story movie tells about Carl Brasshear’s struggle against racism in theUS Navy. After facing all discrimination and racial injustice, Carl succeeded tobecome the first colored people served in the US Navy.Related to the issue of racism occurs in the movie, Lawrence and Kelleherdefined the term of Structural racism as a system of hierarchy and inequity,primarily characterized by white supremacy to maintain their authority overoppressed people. The structural racism occurs in the institution is called asinstitutional racism. As it is shown in the movie, Carl had many obstacles infulfilling his dream caused by racial discrimination. The racial discrimination inthe US Navy is maintained by white supremacy to control their power and toeliminate the opportunity for colored people.This research found out (1) Racism which mostly occurs in the movie is aninstitutional racism where the setting and the story took place in the US Navy asan institution. (2) Spirit, faith, endurance, hard work, and promise to his fatherwere Carl’s strongest motivations to fight against racism. Even though he lost hisone leg, Carl kept struggling to serve as Master Diver and he finally became thefirst amputee to return in full active diving duty. Keywords: Carl Brasshear, racism, struggle, Men of Honor